Integration of empirical and modelled data unravels spatiotemporal distribution and connectivity patterns of Fuegian sprat early life stages - García Alonso, Virginia Andrea (2023)
The distribution patterns of fish early life stages are critical to recruitment successand closely related to major oceanographic circulation patterns. We explored the spatiotemporaldistribution of early life stages of Fuegian sprat Sprattus fuegensis, a key trophic species in the Southwestern Atlantic Ocean (SWAO), in a complex oceanographic setting. Samples were col-lected during austral spring, summer, and autumn, from 2014 to 2017, across areas with distinct biophysical properties between Tierra del Fuego (TDF) and the marine protected area‘Namuncurá’ at Burdwood Bank (BB) (ca. 54°S). Results revealed significant seasonal fluctuations in abundance, distribution, and ontogenetic composition across habitats. High egg and early lar-val abundances at Isla de los Estados (IE) suggest it is an additional spawning ground to those pre-viously identified at TDF and BB. However, only the latter appear to be suitable nursery areas.Particle-tracking simulations based on egg abundance and spawning dates were conducted for the first time using results from a high-resolution hydrodynamic model. Particle transport pro-vides evidence of connectivity between IE and neighbouring areas — enhanced when horizontal diffusivity is incorporated into the model — but not between TDF and BB. Simulated distributionsclosely resembled empirical patterns from this and other studies, allowing the integration ofempirical and modelled data to schematize the species’ dispersal pathways in the study area.These results offer new insights into distribution and connectivity patterns among spawning grounds and highlight the potential use of hydrodynamic models for future assessments of Fue-gian sprat and other planktonic species’ dispersal and recruitment in the SWAO.